Proses Komunikasi Para Perancang Cover Album Musik Independen di Kota Bandung Pada Era 1990-an dan Era 2000-an - Idhar Resmadi; Syarip Hidayat (JURNAL RUPA, 2020)
The city of Bandung has a long history in the development of independent music. This city since the 1990s, gave birth to many independent albums that enliven the Indonesian music industry until recently. Album covers could serve as a vessel to see the development of the visual style of the music subculture. Album cover illustrations have a substantial role as one of the communication media between musicians and listeners (the public). Thus, the role of the album cover designer become central in the independent music subculture. Inevitably, it is important to reassess how the illustrators of album cover music coverings carry out the creative process and the communication process. This study uses qualitative research to determine the context of designing an independent music album cover and its communication aspects. The results of this study are expected to reveal the visualization and influence of communication in the depth between the album designer or illustrator with the independent music subculture in the 1990s and 2000s.